Mutations and structural variants arising during double-strand break repair - Simona Dalin; Sophie Webster; Neal Sugawara; Qiuqin Wu; Shu Zhang; Carmen Macias; Elena Sapède; Tracy Cui; Victoria Liang; Laura Tran; Rameen Beroukhim; James E. Haber (Proceedings of the National Academy of Sciences, 2026)
Double-strand break (DSB) repair is highly mutagenic compared to normal replication. In budding yeast, repair of an HO (homothallism) endonuclease-induced DSB at the mating-type α locus ( MAT α) can be repaired by using an ectopic heterochromatic HMR::Kl-URA3 donor, producing MAT::Kl-URA3 . Among MAT::Kl -Ura3− mutations arising during repair, 50% are base-pair substitutions. 30% are 1-bp indels in short homonucleotide runs, with −1 strongly favored over +1, whereas during replication, spontaneous −1 and +1 events are equal. Microhomology-bounded, repair-associated intragenic deletions (IDs) are recovered 12 times more frequently than tandem duplications (TDs). These data suggest a picture of the structure of the repair replication fork: IDs and TDs occur within the open structure of a migrating D-loop, where the 3’ end of a partly copied new DNA strand can dissociate and anneal with a single-stranded region of microhomology either within ~80 bp ahead or ~40 bp behind the 3’ end. Approximately ~10% of repair-associated mutations are interchromosomal template switches (ICTS), even though the Kluyveromyces lactis URA3 sequence in HMR is only 72% identical (homeologous) with Saccharomyces cerevisiae ura3-52 . ICTS events begin and end at regions of short (~7.5 bp) microhomology; however, ICTS events are constrained to the middle of the copied sequence. Whereas microhomology usage in intragenic deletions is not influenced by adjacent homeology, we show that extensive pairing of adjacent homeology plays a critical role in ICTS. Thus, although by convention, structural variants are characterized by the precise base pairs at their junction, microhomology-mediated template switching actually requires alignment of extensive adjacent homeology.